2017
DOI: 10.3389/fnhum.2017.00636
|View full text |Cite
|
Sign up to set email alerts
|

Altered Volume and Functional Connectivity of the Habenula in Schizophrenia

Abstract: The pathogenesis of schizophrenia (SCH) is associated with the dysfunction of monoamine neurotransmitters, the synthesis and release of which are mainly regulated by a key structure, the habenular (Hb) nucleus. However, little is known regarding whether SCH is associated with structural or functional alterations in the Hb. In this study, we combined structural and resting-state functional magnetic resonance imaging to investigate the changes in volume and functional connectivity of the Hb in 15 patients with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…To our knowledge, there are only two prior neuroimaging studies of the Hb in the clinical populations considered here. Zhang et al ( 52 ) compared the volume, manually segmented using a geometric method, and resting state connectivity of the Hb of 15 patients with SCZ and 16 healthy individuals. They reported bilateral Hb volume reductions with large effect size ( d = −0.84 on the left and d = −0.72 on the right) that did not correlate with the patients' total BPRS scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are only two prior neuroimaging studies of the Hb in the clinical populations considered here. Zhang et al ( 52 ) compared the volume, manually segmented using a geometric method, and resting state connectivity of the Hb of 15 patients with SCZ and 16 healthy individuals. They reported bilateral Hb volume reductions with large effect size ( d = −0.84 on the left and d = −0.72 on the right) that did not correlate with the patients' total BPRS scores.…”
Section: Discussionmentioning
confidence: 99%
“…The study sample ( n = 140) was powered at α = 0.05 and β = 0.20 for an effect size of 0.5 for each case-control comparison. This effect size was chosen as it is large enough to be considered meaningful ( 65 ) while remaining conservative despite the reported effect sizes of approximately 0.7 in the two previous positive studies ( 52 , 53 ). The normality of distribution of the continuous variables of interest was tested using one-sample Kolmogorov–Smirnov test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Peng et al (2018) found that structural connectivity of the lingual gyrus differentiated heavy smokers from light smokers and controls: Heavy smokers had significantly greater white matter atrophy of the lingual gyrus. Although no previous research has found aberrant habenula-lingual connectivity in smokers, habenula-lingual abnormalities in individuals with schizophrenia (Zhang et al, 2017) and high "negative connectivity" between the habenula and lingual gyrus in both healthy controls and psychiatric patients have been reported (Curtis et al, 2017;Ely et al, 2016).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 91%
“…Jacinto et al also found that rats exposed to chronic, unpredictable stress had reduced volumes of MHb and LHb in both hemispheres and had lower number of cells in their right MHb and bilateral LHb areas [11]. However, functional magnetic resonance imaging (fMRI) studies have failed to identify significant differences for major depressive disorder (MDD) and healthy control groups [12][13][14]; meanwhile, analysis of schizophrenia patients showed atrophy of their Hb volume compared with controls [15]. Such differences might be due to the insufficient resolution of the imaging methods used and/or inaccurate measurement of the volumes post tissue processing and 3D reconstitution of the volumes.…”
Section: Introductionmentioning
confidence: 99%